Who Gains from Active Learning in Higher Education? - Giulio Bosio; Federica Origo (Institute of Labor Economics (IZA), 2019)
The aim of this paper is to study whether and how teaching style (i.e., traditional vs active mode) affects academic performance of young individuals in tertiary education. We focus on entrepreneurship education as an ideal subject for experimenting alternative teaching methods. Identification relies on Triple Differences (DDD) estimates based on detailed administrative data for the universe of students in a Master's program in Management and Finance in Italy over 2011-2015. We measure academic achievement through several indicators, both right after the end of the entrepreneurship course (short run) and at the end of the program (long run). Our preferred estimates show no significant effects of the teaching mode on student's achievement, both in the short and in the long run. However, further estimates reveal interesting heterogeneities across students, being active teaching more effective in the case of females and students from secondary schools with an academic track.
Keywords: I20; J24; L26; 330; entrepreneurship education; teaching modes; academic performance; triple difference; difference-in-differences